Medical titanium alloy with biological multifunctionality and manufacturing method thereof
By depositing AG+-ha/Zn2+-FE3O4 micro-structures and using external magnetic fields in the medical titanium alloy surface, it solves the problem of titanium alloy in the human body to promote osteosoplasty adhesion and insufficient antibacteriality, and achieve antibacterial and antibacterial and realizable. The bone inducement function meets the needs of biological versatile.
Patent Information
- Application Number
- CN202411482355.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-28
AI Technical Summary
After being implanted into the human body, medical titanium alloys are difficult to promote the adhesion and growth of bone cells, and are insufficient antibacterial properties, which can easily lead to bacterial infections and cannot meet the needs of biological multifunctionalization.
By depositing AG+-ha/Zn2+-FE3O4 microstructure on the surface of the medical titanium alloy, using the antibacterial function of silver ions, the bone inducement function of calcium hydroxide, and the bone repair function of magnetic nanoparticles, combined with the incentive effect of the external magnetic field, realize the titanium alloy Antibacterial and bone induction function.
It significantly improves the antibacterial and bone inducement function of medical titanium alloy, enhances the intensity of the implant and bone tissue, reduces the risk of bacterial infection, and meets the needs of biological multifunctionalization.
Smart Images

Figure CN119367593A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the structure and preparation of a medical titanium alloy, in particular to a medical titanium alloy with biological multifunctionality and a manufacturing method thereof. Background Art
[0002] Titanium and titanium alloys are widely used in the manufacture of bone implants due to their good biocompatibility, but they are biologically inert metal materials, mainly due to the TiO2 passivation film layer on the surface of titanium alloys, which makes it difficult for new bone cells and other biological tissues to attach, grow and fuse on their surface. At the same time, titanium alloy bone implants are only surrounded by a layer of encapsulation fibers after being implanted in the human body, and the mechanical locking strength formed between the titanium alloy and the matrix tissue is relatively small. During long-term load-bearing service, they will gradually loosen, causing the implant to fail prematurely and requiring another surgery, causing additional pain and economic burden on patients. In addition, the antibacterial activity of medical titanium and titanium alloys is weak, which makes it easy for bacteria to adhere to the implant after it is implanted in the human body, and then cause bacterial infection. Medical titanium and titanium alloys have no biological activity and antibacterial properties after being implanted in the human body, and cannot meet the current biological multifunctional requirements of human implant devices such as antibacterial and bone induction activity.
[0003] In recent years, surface modification methods have become an important way to solve the above problems. For example, hydroxyapatite (HA) particles are melted and deposited on the surface of titanium alloy by plasma spraying, laser cladding and other processes, and then cooled to obtain HA coating. This process method is highly efficient, but there are obvious differences in physical and chemical properties between the coating and the substrate, especially the difference in thermal expansion coefficient, which leads to cracks and even shedding at the junction of the two. Antibacterial particles doped HA coatings are deposited on the surface of titanium alloys through electrolyte composition design by electrophoretic deposition, bionic mineralization and sol-gel methods to improve the antibacterial properties of HA and avoid cracking of the coating due to residual thermal stress. The above surface modification methods have improved the biological function of titanium alloys to a certain extent, but due to the difference in physical properties between the coating and the titanium alloy substrate, and under load conditions after implantation in the human body, the interface stress between the coating and the alloy substrate is large, resulting in low interface bonding strength, which can easily lead to premature failure of the biological coating, thereby leading to the loss of its biological function. Summary of the invention
[0004] Purpose of the invention: The purpose of the present invention is to provide a medical titanium alloy having multiple biological functions such as antibacterial and bone induction.
[0005] Another object of the present invention is to provide a method for manufacturing a medical titanium alloy having multiple biological functions such as antibacterial and bone induction and a simple process.
[0006] Technical solution: The titanium alloy with biological multifunctionality described in the present invention comprises a matrix, the surface of which has Ag with magnetic, antibacterial and bone induction functions.+ -HA / Zn 2+ -Fe3O4 microstructure.
[0007] Preferably, Ag + -HA / Zn 2+ -Fe3O4 microstructure for loading antibacterial Ag + HA coated with Zn loaded osteoinductive 2+ The surface of magnetic Fe3O4 nanoparticles.
[0008] Preferably, the substrate is a medical titanium alloy.
[0009] A method for preparing a titanium alloy comprises the following steps:
[0010] (1) FeCl3, FeCl2 and ZnCl2 are dissolved in an ethanol / water mixed solution and mixed and stirred, and NaOH solution is slowly added and stirred continuously;
[0011] (2) dissolving ammonium hydrogen phosphate in an ethanol / water mixed solution and stirring, adding AgNO3 and calcium nitrate aqueous solution, slowly adding NaOH solution to adjust the pH value, and continuing stirring;
[0012] (3) Mixing and stirring the solutions obtained in step (1) and (2), pouring into a reaction kettle for reaction, and sintering at high temperature after the reaction to obtain Ag + -HA / Zn 2+ -Fe3O4 magnetic nano-functional particles;
[0013] (4) fixing the medical titanium alloy on a magnet and placing it in the aqueous solution of the magnetic nano-functional particles in step (3) to obtain a titanium alloy with magnetic particles deposited on the surface;
[0014] (5) Using a femtosecond laser beam, the titanium alloy surface on which the magnetic particles were deposited in step (4) was quickly scanned to obtain Ag with magnetic / antibacterial / bone induction properties. + -HA / Zn 2+ -Fe3O4 multifunctional microstructure.
[0015] Preferably, the concentration ratio of FeCl3, FeCl2 and ZnCl2 in step (1) is 2:1:1 to 2:1:0.5; preferably 3:1.5:1; the concentration of NaOH is 0.1-0.2 mol / L, preferably 0.1 mol / L.
[0016] Preferably, in step (2), the concentration ratio of ammonium hydrogen phosphate to calcium nitrate is 12:1-6:1, preferably 12:1; the concentration of calcium nitrate is 0.1-0.2 mol / L, preferably 0.2 mol / L; the concentration of AgNO3 is 0.05-0.1 mol / L, preferably 0.1 mol / L; the concentration of NaOH is 0.1-0.2 mol / L, preferably 0.1 mol / L; and the pH value of the solution is adjusted to 11-12.
[0017] Preferably, the reaction temperature in step (3) is 100-300°C, preferably 200°C; the reaction time is 8-15h, preferably 10h; and the high-temperature sintering temperature is 350-500°C, preferably 500°C.
[0018] Preferably, the concentration of the magnetic nano-functional particles in step (4) is 0.2-0.5 mol / L, preferably 0.5 mol / L; the magnetic field strength is 0.1-0.5 T, preferably 0.5 T.
[0019] Preferably, the power of the laser beam in step (5) is 0.5 to 1.5 W, preferably 1.5 W.
[0020] Invention principle: According to the biological multifunctional requirements of medical titanium alloy bone implants, based on the bone repair and sterilization functions produced by the magnetothermal and magnetic physical effects of magnetic nanoparticles, a multifunctional ion-doped magnetic Fe3O4 nanoparticle material was designed. + HA coated with osteoinductive Zn 2+ doped Fe3O4 nanoparticles; secondly, the medical titanium alloy is fixed on the surface of the magnet and placed in an aqueous solution dispersed with multifunctional nanoparticles. The magnetic nanoparticles are driven to deposit on the surface of the titanium alloy under the action of the magnetic field. The synergistic effect of the micro-area molten pool tension and the magnetic field force generated by the femtosecond laser beam scanning the surface of the medical titanium alloy is used to promote the doping and dispersion of magnetic nanoparticles in the microstructure, thereby realizing the manufacture of a microstructure loaded with multifunctional magnetic nanoparticles on the surface of the medical titanium alloy.
[0021] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:
[0022] 1. Based on the excellent antibacterial function of silver ions, the good bone induction function of Zn ions and HA, and the bone repair and bactericidal function of magnetic nanoparticles under the stimulation of an external magnetic field, an in-situ multi-ion doping method was used to prepare a nanostructured nanoparticle loaded with antibacterial Ag. + HA coated with osteoinductive Zn 2+ Doped Fe3O4 nanoparticles endow magnetic nanoparticles with biological multifunctionality such as antibacterial / bone induction.
[0023] 2. Aiming at the biological inertness of medical titanium alloys, based on the induction growth characteristics of microstructure on bone tissue and Ag + -HA / Zn 2+ -Biological functions of Fe3O4, designed antibacterial Ag + Loaded on HA and coated with osteoinductive Zn 2+ The microstructure of the surface of magnetic Fe3O4 nanoparticles, with the help of the stimulation of the external magnetic field, effectively improves the bone induction and antibacterial function of the surface of medical titanium alloy.
[0024] 3. Based on Ag + -HA / Zn 2+ -Based on the magnetic function of Fe3O4 nanoparticles and the excitation effect of the external magnetic field, a manufacturing method for the surface microstructure of medical titanium alloy doped with magnetic functional particles was designed to realize the manufacturing of magnetic functional nanoparticle-doped microstructures. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a microscopic morphology of the titanium alloy with a multifunctional structure on the surface manufactured in Example 1;
[0026] Figure 2 This is a comparison chart of the relative expression of alkaline phosphatase of the titanium alloys with multifunctional structures on the surface manufactured in Examples 2 and 3 and Comparative Example 1 after being cultured for 14 days. DETAILED DESCRIPTION
[0027] The technical solution of the present invention is further described below in conjunction with embodiments.
[0028] Example 1
[0029] The bio-multifunctional medical titanium alloy of the present invention comprises Ag having magnetic, antibacterial and bone-inducing functions on the surface of the medical titanium alloy. + -HA / Zn 2+ -Fe3O4 microstructure; Ag + -HA / Zn 2+ -Fe3O4 functional microstructure for loading antibacterial Ag + HA coated with Zn loaded osteoinductive 2+ The surface of magnetic Fe3O4 nanoparticles.
[0030] The method for preparing the medical titanium alloy of the present invention comprises the following steps:
[0031] (1) Dissolve 0.1 mol / L FeCl3, 0.05 mol / L FeCl2 and 0.05 mol / L ZnCl2 powder in a 1:1 ethanol / water mixed solution and stir for 10 to 15 minutes, slowly add 0.1 mol / L NaOH solution to the mixed solution, and continue stirring for 10 to 15 minutes;
[0032] (2) Dissolve 0.6 mol / L ammonium hydrogen phosphate powder in a 1:1 ethanol / water mixture and stir, add 0.05 mol / L AgNO3 and 0.1 mol / L calcium nitrate aqueous solution, and then slowly add 0.1 mol / L NaOH solution until the pH value of the solution is 11-12, and continue stirring for 10-30 min;
[0033] (3) The solutions obtained in step (1) and (2) were mixed and stirred, poured into a reaction kettle, kept at 200°C for 10 hours, cooled to room temperature, dried, and sintered at 350°C to obtain Ag. + -HA / Zn 2+ -Fe3O4 magnetic nano-functional particles;
[0034] (4) fixing the medical titanium alloy on a 0.1 T magnet and placing it in the 0.2 mol / L aqueous solution of magnetic nano-functional particles described in step (3) to obtain a titanium alloy with magnetic particles deposited on the surface;
[0035] (5) Using a femtosecond laser beam with a power of 0.5 W, the titanium alloy surface on which the magnetic particles were deposited in step (4) was quickly scanned to obtain Ag with magnetic / antibacterial / bone induction properties. + -HA / Zn 2+ -Fe3O4 multifunctional microstructure.
[0036] according to Figure 1 It can be seen that the surface of the titanium alloy is distributed with mutually parallel microstructures, whose width is about 0.5μm; at the same time, Ag is distributed on the surface of the microstructure + -HA / Zn 2+ -Fe3O4 white particles have a significant promoting effect on the induction growth and antibacterial effect of bone tissue.
[0037] Example 2
[0038] (1) Dissolve 0.3 mol / L FeCl3, 0.15 mol / L FeCl2 and 0.1 mol / L ZnCl2 powder in a 1:1 ethanol / water mixed solution and stir for 10 to 15 minutes, slowly add 0.1 mol / L NaOH solution to the mixed solution, and continue stirring for 10 to 15 minutes;
[0039] (2) Dissolve 0.6 mol / L ammonium hydrogen phosphate powder in a 1:1 ethanol / water mixture and stir, add 0.05 mol / L AgNO3 and 0.1 mol / L calcium nitrate aqueous solution, and then slowly add 0.1 mol / L NaOH solution until the pH value of the solution is 11-12, and continue stirring for 10-30 min;
[0040] (3) The solutions obtained in step (1) and (2) were mixed and stirred, poured into a reaction kettle, kept at 200°C for 10 hours, cooled to room temperature, dried, and sintered at 450°C to obtain Ag. + -HA / Zn 2+ -Fe3O4 magnetic nano-functional particles;
[0041] (4) fixing the medical titanium alloy on a 0.3 T magnet and placing it in the 0.2 mol / L aqueous solution of magnetic nano-functional particles described in step (3) to obtain a titanium alloy with magnetic particles deposited on the surface;
[0042] (5) Using a femtosecond laser beam with a power of 0.5 W, the titanium alloy surface on which the magnetic particles were deposited in step (4) was quickly scanned to obtain Ag with magnetic / antibacterial / bone induction properties. + -HA / Zn 2+ -Fe3O4 multifunctional microstructure.
[0043] Example 3
[0044] (1) Dissolve 0.3 mol / L FeCl3, 0.15 mol / L FeCl2 and 0.1 mol / L ZnCl2 powder in a 1:1 ethanol / water mixed solution and stir for 10 to 15 minutes, slowly add 0.1 mol / L NaOH solution to the mixed solution, and continue stirring for 10 to 15 minutes;
[0045] (2) Dissolve 1.2 mol / L ammonium hydrogen phosphate powder in a 1:1 ethanol / water mixture and stir, add 0.1 mol / L AgNO3 and 0.2 mol / L calcium nitrate aqueous solution, and then slowly add 0.1 mol / L NaOH solution until the pH value of the solution is 11-12, and continue stirring for 10-30 min;
[0046] (3) The solutions obtained in step (1) and (2) were mixed and stirred, poured into a reaction kettle, kept at 200° C. for 10 h, cooled to room temperature, dried, and sintered at 500° C. to obtain Ag. + -HA / Zn 2+ -Fe3O4 magnetic nano-functional particles;
[0047] (4) fixing the medical titanium alloy on a 0.5 T magnet and placing it in the 0.5 mol / L aqueous solution of magnetic nano-functional particles described in step (3) to obtain a titanium alloy with magnetic particles deposited on the surface;
[0048] (5) Using a femtosecond laser beam with a power of 1.5 W, the titanium alloy surface on which the magnetic particles were deposited in step (4) was quickly scanned to obtain Ag with magnetic / antibacterial / bone induction properties. + -HA / Zn 2+ -Fe3O4 multifunctional microstructure.
[0049] Comparative Example 1
[0050] The similarities between this embodiment and embodiment 1 are not repeated here, except that only 0.5W femtosecond laser is used to scan the surface of the medical titanium alloy. The titanium alloy surface obtained by this method forms a microstructure, but does not have magnetic, antibacterial, bone induction and other functions.
[0051] Test and result analysis of antibacterial rate: Staphylococcus aureus was selected as the test object, and Escherichia coli was tested for 72 hours in Example 2-3 and Comparative Example 1 according to QB / T2591-2003 "Antibacterial Plastics-Antibacterial Performance Test Method and Antibacterial Effect" to obtain the antibacterial rate. The antibacterial rate of the multifunctional structure on the surface of the titanium alloy prepared in Examples 2 and 3 against Escherichia coli after 72 hours of the test was 99.996%, which was higher than the antibacterial rate of the single silver coating of 99.916% (Ding Jia. Preparation of Ag coating on titanium alloy surface and study on its antibacterial performance [D]. Guilin University of Electronic Technology, 2023.), while the titanium alloy with a single microstructure in Comparative Example 1 had no antibacterial property.
[0052] Test and result analysis of bone induction function: The multifunctional microstructure surface prepared in Examples 1-3 and Comparative Example 1 was inoculated with 10 5 BMSCs cells were cultured in a culture medium containing ascorbic acid, dexamethasone, and p-glycerophosphate for 14 days, and the ALP activity value was detected using an alkaline phosphatase kit. Figure 2 It can be seen that the ALP values of Examples 1, 2 and 3 are relatively high, all better than the gene expression value of the single microstructure prepared by femtosecond laser in Comparative Example 1. This shows that the microstructure doped with magnetic functional particles prepared by this method promotes osteoblast differentiation, enhances bone formation ability, and thus accelerates bone defect repair, effectively improving bone induction function. This further shows that the titanium alloy prepared by this method has excellent antibacterial function and cell growth promotion function, thereby improving biological activity.
Claims
1. A titanium alloy with bio-multifunctionality, characterized in that: It includes a matrix, the surface of which has Ag that integrates magnetic, antibacterial and bone induction functions. + -HA / Zn 2+ -Fe3O4 microstructure.
2. The titanium alloy with bio-multifunctionality according to claim 1, characterized in that: The Ag + -HA / Zn 2 + -Fe3O4 microstructure for loading antibacterial Ag + HA coated with Zn loaded osteoinductive 2+ The surface of magnetic Fe3O4 nanoparticles.
3. The titanium alloy with bio-multifunctionality according to claim 1, characterized in that: The matrix is medical titanium alloy.
4. A method for preparing the titanium alloy according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) FeCl3, FeCl2 and ZnCl2 are dissolved in an ethanol / water mixed solution and mixed and stirred, and NaOH solution is slowly added and stirred continuously; (2) dissolving ammonium hydrogen phosphate in an ethanol / water mixed solution and stirring, adding AgNO3 and calcium nitrate aqueous solution, slowly adding NaOH solution to adjust the pH value, and continuing stirring; (3) Mixing and stirring the solutions obtained in step (1) and (2), pouring into a reaction kettle for reaction, and sintering at high temperature after the reaction to obtain Ag + -HA / Zn 2+ -Fe3O4 magnetic nano-functional particles; (4) fixing the medical titanium alloy on a magnet and placing it in the aqueous solution of the magnetic nano-functional particles in step (3) to obtain a titanium alloy with magnetic particles deposited on the surface; (5) Using a femtosecond laser beam, the titanium alloy surface on which the magnetic particles were deposited in step (4) was quickly scanned to obtain Ag with magnetic / antibacterial / bone induction properties. + -HA / Zn 2+ -Fe3O4 multifunctional microstructure.
5. The preparation method according to claim 4, characterized in that: The concentration ratio of FeCl3, FeCl2 and ZnCl2 in step (1) is 2:1:1 to 2:1:0.5; the concentration of NaOH is 0.1-0.2 mol / L.
6. The preparation method according to claim 4, characterized in that: In step (2), the concentration ratio of ammonium hydrogen phosphate to calcium nitrate is 12:1-6:1; the concentration of calcium nitrate is 0.1-0.2 mol / L; the concentration of AgNO3 is 0.05-0.1 mol / L; the concentration of NaOH is 0.1-0.2 mol / L; and the pH value of the solution is adjusted to 11-12.
7. The preparation method according to claim 4, characterized in that: The reaction temperature in step (3) is 100-300°C, and the reaction time is 8-15h; the high-temperature sintering temperature is 350-500°C.
8. The preparation method according to claim 4, characterized in that: In step (4), the concentration of the magnetic nano-functional particles is 0.2-0.5 mol / L, and the magnetic field strength is 0.1-0.5 T.
9. The preparation method according to claim 4, characterized in that: The power of the laser beam in step (5) is 0.5 to 1.5 W.
10. The preparation method according to claim 4, characterized in that: The power of the laser beam in step (5) is 1.5W.